PENERAPAN METODE LANGSUNG DALAM MENINGKATKAN KEMAMPUAN BERBICARA MAHASISWA PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Cicilia Donalda; Yoanna Afrimonika; Tjen Veronica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
As we all know, Mandarin is an international language. In today's society, many people are interested and want to learn Chinese. In the process of learning Mandarin, listening, speaking, reading and writing are the four skills that students must learn. In order to communicate well, students need to learn listening and speaking skills first. Before doing the research, the writer looked for and read the learning theory. It was found that there is a foreign language teaching method called the direct teaching method as an effective oral teaching method because it focuses on the oral aspect. The direct teaching method means that the teacher but uses the target language to explain and communicate with students during learning. The purpose of this writing is to determine the effect of the direct method on the speaking abilities of Class A Mandarin Language Education Study Program Students Class 2022 FKIP UNTAN. This study uses test questions and questionnaires to obtain research results. The results of the research show that the direct teaching method has improved students speaking skills. The students' average score on the pretest was 67. And the average score on the posttest was 79.4. After being analyzed, the authors found that the direct method fits perfectly with the student learning method. Most students feel that the direct teaching method is very effective, which can make students listen to the class more serious and active, and make students more confident in using Mandarin to communicate.